ANALYSIS PLANNING NEEDS USING HEALTH WORKLOAD ANALYSIS METHOD (ABK-KES) FOR MEDICAL RECORDING PERSONNEL IN HOSPITAL: LITERATURE REVIEW - A, Rachmawati; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT The planning of human resource requirements is a series of systematic and strategic activities related to forecasting the needs of employees in the future within an organization (public or business) and using relevant information resources for the provision of human resources in the required quantity and quality. Uneven distribution among healthcare workers will have an impact on the quality of healthcare services, which is not optimal. The purpose of this research is to conduct a review of several pieces of literature related to the human resource planning process using the Health Workload Analysis Method. This research employs a literature review design. The method used in this literature review is a systematic mapping study using the keywords HR planning, health workload analysis, medical recorder, hospital. The article in this research used an interval of 5 years (2018–2022). Then, the research area only focused on the hospital. Furthermore, the result of filtering is in accordance with the inclusion criteria and exclusion research article. Therefore, it has gained five research articles. The results of the study article showed that not all job descriptions of medical records officers were in accordance with their job descriptions. It was affected by the shortage of medical record officers, which caused them to have more than one job Therefore, it is necessary to add additional medical records officers in accordance with the workload analysis so that medical records services run optimally, effectively and efficiently. Keywords: Human Resources, Health Workload Analysis Method, Medical Records, and Hospital